Comparison of bacterial intracellular and secreted proteins produced in milk versus medium for Escherichia coli by proteomic analysis - Qiyue Sun; Yanxin Li; Hongning Jiang; Qijing Du; Jun Wang; Rongbo Fan; Rongwei Han; Yongxin Yang (Journal of Dairy Science)
ABSTRACT: The growth and reproduction of microorganisms are dependent on nutrient supply. Here, milk and Luria-Bertani (LB) media were used as nutrition sources for Escherichia coli, and the changes in bacterial and secretory proteins at 3 time points (3, 9, and 18 h) in the growth cycle were studied using a label-free proteomics technique. The findings revealed that the abundances of bacterial intracellular proteins inosine/xanthosine triphosphatase and universal stress protein F increase dramatically during the growth phase in milk and LB media. In terms of secretory proteins, RNase PH and tyrosine-tRNA ligase abundance increased dramatically, and outer membrane protein X and outer membrane protein C abundance decreased significantly from 3 to 18 h in both milk and LB media. Several bacterial intracellular and secretory proteins showed media-dependent changes, including hydrogenase-2 and s-adenosylmethionine synthase, which were only found in the LB medium. In contrast, DNA polymerase III subunit α and cold shock-like protein CspD (CspD) were discovered only in milk. The 2 media shared the differential abundance of proteins involved in small molecule binding and small molecule metabolic process pathways. The differentially expressed intracellular proteins of E. coli cultured in milk were associated with membrane trafficking and signal transduction pathways. The findings improve our understanding of changes in E. coli bacterial intracellular proteins and secretory proteins in response to nutritional stimuli, as well as provide a new perspective and foundation for investigating its adaptive mechanisms in a variety of environments, potentially leading to better prevention and control strategies.